Salicylic acid increases flavonolignans accumulation in the fruits of hydroponically cultured Silybum marianum - Hayam S. Ahmed; Abeer S. Moawad; Sameh F. AbouZid; Asmaa I. Owis (Elsevier, 2020)
Silybum marianum (L.) Gaertn. (Asteraceae) was hydroponically cultured using a nutrient film technique system. Silibinin, isosilibinin and silychristin were detected in the fruits of the cultured plants. The effect of salicylic acid on the improvement of flavonolignans production by the fruits of the hydroponically cultured S. marianum was investigated. Salicylic acid was added to the nutrient solution at different concentrations (100, 200 and 400 µM) and the mature fruits of the plant were collected five days after elicitor addition. The fruits were then analyzed for their total flavonolignans contents and individual components using quantitative proton nuclear magnetic resonance spectroscopy (qHNMR) and high-performance liquid chromatography (HPLC). The results showed that elicitation with salicylic acid at 200 µM for five days increased production of total flavonolignans (1.7-fold by qHNMR and 1.6-fold by HPLC) higher than the control cultures and (1.4-fold by qHNMR and 1.1-fold by HPLC) higher than the cultivated plants. Silychristin was the major flavonolignan produced by the cultured plant. Elicitation by 200 µM salicylic acid increased silychristin production (1.6-fold by qHNMR and HPLC) higher than the control cultures and (1.3-fold by qHNMR and 1.0-fold by HPLC) higher than the cultivated plants. The present study provides a chance to improve secondary metabolite yield, serves as a useful tool for studying the biosynthesis of these medicinally valuable compounds and its regulation in plant and spots more light on hydroponic system as an important agricultural technique.